Epidemiology of Ophthalmologic Disease Associated with Erythema Multiforme, Stevens‐Johnson Syndrome, and Toxic Epidermal Necrolysis in Hospitalized Children in the United States. Issue 2 (16th May 2013) - Moreau, Jacqueline F.; Watson, Robert S.; Hartman, Mary E.; Linde‐Zwirble, Walter T.; Ferris, Laura K.
Abstract The objective of the current study was to characterize the epidemiology and resource use of U.S. children hospitalized with ophthalmologic disease secondary to erythema multiforme (EM), Stevens‐Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN). We studied children ages 5 to 19 years hospitalized in 2005 in 11 states, encompassing 38% of the U.S. pediatric population. Using International Classification of Diseases, Ninth Revision, Clinical Modification codes, we identified admissions of children with EM, SJS, or TEN and the presence of concurrent ophthalmologic disease, analyzed patient and hospitalization characteristics, and generated age‐ and sex‐adjusted national estimates. We identified 460 children admitted with EM, SJS, or TEN, corresponding to 1, 229 U.S. hospitalizations in 2005. Of the children with EM, SJS, or TEN, 60 (13.0%) had ophthalmologic disease, primarily (90.0%) disorders of the conjunctiva. Children with the highest proportions of ophthalmologic disease included those with mycoplasma pneumonia (26.7%), herpes simplex virus (15.6%), upper respiratory infection (13.9%), and lower respiratory infection (13.7%). Individuals with EM, SJS, or TEN and ophthalmologic disease were more likely than those without ophthalmologic disease to receive intensive care unit care (28.3% vs 17.0%, p = 0.03) and to be admitted to a children's hospital (63.3% vs 48.8%, p = 0.03). Ophthalmologic disease was also associated with a significantly longer median length of stay (6.0 days, interquartile range [IQR] 3–9 days vs 3.0 days, IQR 2–6 days, p < 0.001) and median hospital cost (7, 868, IQR 3, 539–17, 440 vs 2, 969, IQR 1, 603–8, 656, p < 0.001). In children with EM, SJS, or TEN, ophthalmologic disease was most common in those with concurrent Mycoplasma pneumoniae and herpes simplex virus infections. Ophthalmologic disease was associated with considerably higher inpatient resource use in this population. Children with EM, SJS, or TEN should be screened and treated early for ophthalmologic disease to prevent morbidity and minimize long‐term sequellae.